2012
DOI: 10.1175/jcli-d-11-00518.1
|View full text |Cite
|
Sign up to set email alerts
|

The 1960s Drought and the Subsequent Shift to a Wetter Climate in the Catskill Mountains Region of the New York City Watershed*

Abstract: The precipitation history over the last century in the Catskill Mountains region that supplies water to New York City is studied. A severe drought occurred in the early to mid-1960s followed by a wet period that continues. Interannual variability of precipitation in the region is related to patterns of atmospheric circulation variability in the midlatitude east Pacific-North America-west Atlantic sector with no link to the tropics. Associated SST variations in the Atlantic are consistent with being forced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 42 publications
3
89
0
1
Order By: Relevance
“…However, our results and the recent work of others (Kingston et al 2007, Seager et al 2012 suggest that observed changes in flooding are at most complexly, and not exclusively, related to the NAO via its potential influence on storm tracks and antecedent soil moisture conditions. Floods are episodic phenomena, so we should also consider other recently documented changes in North Atlantic basin atmospheric conditions that may also affect conditions at the event scale.…”
Section: Our Findings Lead To Several Important Questionssupporting
confidence: 56%
See 3 more Smart Citations
“…However, our results and the recent work of others (Kingston et al 2007, Seager et al 2012 suggest that observed changes in flooding are at most complexly, and not exclusively, related to the NAO via its potential influence on storm tracks and antecedent soil moisture conditions. Floods are episodic phenomena, so we should also consider other recently documented changes in North Atlantic basin atmospheric conditions that may also affect conditions at the event scale.…”
Section: Our Findings Lead To Several Important Questionssupporting
confidence: 56%
“…In agreement, Polsky et al (2000) found a 10% increase in MAR monthly mean precipitation over the 20th century. Increases have been especially pronounced in the northeastern US (Groisman et al 2004, Madsen and Figdor 2007, Douglas and Fairbank 2011, Nguyen and DeGaetano 2012, Seager et al 2012. Regional temperatures have also increased over the 20th century (Groisman et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of the 1960s drought is a subject of debate [12,13,54] and future research is needed to better understand it so that future droughts can be better anticipated. …”
Section: Conclusion and Discussionmentioning
confidence: 99%